Molding the Audience: On the Genesis of Effect in Audiovisual Discourse - Ivan Marino (International Journal of Film and Media Arts, 2017)
The following paper explores the first Soviet essays aimed at researching the role of "effect" in audiovisual discourse, relating them in turn to the main schools of thought of the time. The aim of this research is to return to the sources of audiovisual rhetoric - one of the most effective and persuasive discursive techniques of contemporary culture - to elliptically identify its reminiscences in current cinema and TV discourses. Following this line of work, we analyze, among others, the first ideas of Pudovkin (2006), Kuleshov (1974) and Eisenstein (2010a) on the subject, focusing on the notions of «attraction» and «effect» that, in our opinion, remain transformed in the audiovisual discourses of today.